2017
DOI: 10.3390/su9081225
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Traits of Relevance to Sustainability of Smallholder Sheep Farming Systems in South Africa

Abstract: Sustainable livestock production is important to ensure continuous availability of resources for future generations. Most smallholder livestock farming systems in developing countries have been perceived to be environmentally, socially and economically unsustainable. Farming with livestock that is robust and adaptable to harsh environments is important in developing countries especially in semi-arid and arid environments. This review discusses the different sheep farming systems employed by smallholder farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 73 publications
(109 reference statements)
0
14
0
Order By: Relevance
“…The initially domesticated sheep breeds in West Africa have also been genetically mixed with European breeds (Brahi et al, 2015). Using the OvineSNP50 beadchip, Molotsi et al (2017) reported that the smallholder Dorper sheep was introgressed with Namaqua Afrikaner, South African Mutton Merino and White Dorpers genes. They further reported that the smallholder Dorper population was more genetically diverse than the pure-bred Dorper, South African Mutton Merino and Namaqua Afrikaner.…”
Section: African Livestock Productivity In the Era Of Genomic Breedingmentioning
confidence: 99%
“…The initially domesticated sheep breeds in West Africa have also been genetically mixed with European breeds (Brahi et al, 2015). Using the OvineSNP50 beadchip, Molotsi et al (2017) reported that the smallholder Dorper sheep was introgressed with Namaqua Afrikaner, South African Mutton Merino and White Dorpers genes. They further reported that the smallholder Dorper population was more genetically diverse than the pure-bred Dorper, South African Mutton Merino and Namaqua Afrikaner.…”
Section: African Livestock Productivity In the Era Of Genomic Breedingmentioning
confidence: 99%
“…Smallholder livestock farmers play a major role in enhancing livestock production in South Africa. South Africa has an estimated 28.8 million sheep, of which 7.4 million are owned by smallholder farmers and 21.4 million owned by commercial farmers (Molotsi et al 2017). This shows that commercial farmers who produce and supply the local and international markets dominate the sheep industry in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as, consumer preferences, changing lifestyle, globalisation, high population and income growth have increased the demand for sheep and sheep products in the local market (Rios et al 2009). Climate change especially drought and increasing production cost has slowed down sheep production in South Africa (Molotsi et al 2017). This gap between demand for and supply of sheep and sheep products has provided a great opportunity for integrating smallholder sheep farmers into the value chain (Ndoro et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these factors that hinder viable utilization of these ovine genetic resources in rural communities include poor feed resources, poor record keeping, lack of structured breeding programs, disease and health challenges, poor market access, ageing male farmers since the youth and females are unwilling to farm, as well as a lack of technical skills and knowledge. Smallholder farmers practice communal farming, or those benefiting from the land reform and redistribution program (LRAD) farm with the assistance of a mentor [38]. The mentor is a commercial farmer who already has a successful farming enterprise.…”
Section: Sustainable Utilisation Of Ovine Genetic Resourcesmentioning
confidence: 99%